Las adaptaciones de La cerillera, de H. Ch. Andersen: posibilidades expresivas y planteamientos éticos en la representación del trabajo infantil - Cuvardic García, Dorde (2014)
The little match girl was a common child street social type on XIX century’s cultural representations. Although a couple of cases which positively sanctioning children’s matches sales are found, as in “El cerillero”, from the costumbrist collection Los niños pintados por ellos [sic] mismos (1841), the most important function of XIX century´s narrative showing this street trade was to awaken public opinion attention to social vulnerability and child labor issues. In this sense, an important milestone was Hans Christian Andersen’s short story The Little Match Girl (1845), which in the following decades was adapted on magic lantern shows (The Little Match Girl, 1905, 9’), fictional silent movies (The Little Match Girl, 1914, 10’) and, a few years back, on a Disney’s animated short feature (The Littlematch Girl, 2006, 7’). In this article, we analyze and interpret the stylistic and narrative differences of these three adaptations, from the various expressive possibilities of the media used, as well as the historical development of the ideological construct of childhood.